The Communal Elections from 1930: Case studies – Slimnic and Presaca Communes, Sibiu County - UNGUREANU-ILINCA, Ana-Maria (Studia Universitatis Babeș-Bolyai Historia, 2022)
The parliamentary elections play a special role in Romanian historiography, but we still need many studies on the local ones. The study aims to focus on how political life occurred in rural areas after the achievement of the administrative unification. Following that newly created context, we intend to capture how the electoral campaign is carried out at the local level. We analyse the changes in the Romanian electoral system, primarily focusing on the local elections in the rural area of Sibiu. From a methodological point of view, we studied the press of the period and archival documentary sources. We have focused on the communal electoral lists, which we analysed with the support of a database. Our approach, based on a quantitative statistic-sociological classification of the candidates, and of the voters from the communal elections in Sibiu County, reveals how involved the peasants were in political affairs. At the same time, this paper elucidates, through archival evidence, how authorities interfered in the mechanisms of the electoral process. Rezumat: Alegerile parlamentare joacă un rol important în istoriografia românească, dar avem încă nevoie de studii asupra celor locale. Studiul îşi propune să se concentreze asupra modului în care a apărut viața politică în zona rurală, după ce a fost realizată o unificare administrativă. Urmărind contextul nou creat, studiul are intenția să captureze modul în care campania electorală s-a desfăşurat la nivel local. Studiul analizează schimbările în sistemul electoral românesc, concentrându-se asupra alegerilor locale din zona rurală din proximitatea Sibiului. Din punct de vedere metodologic, am studiat presa epocii şi surse de arhivă. Ne-am concentrat asupra listelor electorale comunale, pe care le-am analizat cu ajutorul unei baze de date. Abordarea, bazată pe o clasificare cantitativă, statistică, sociologică a candidaților şi a electoratului participant la alegerile comunale din regiunea Sibiu, relevă nivelul de implicare a țărănimii în activitatea politică. În acelaşi timp, studiul elucidează, cu ajutorul documentelor de arhivă, modul în care autoritățile au intervenit în mecanismele procesului electoral. Cuvinte-cheie: alegeri comunale, sistem electoral, candidați, partide politice, propagandă, rezultate electorale